Rancangan Sistem Keamanan Jaringan dari serangan DDoS Menggunakan Metode Pengujian Penetrasi - Mamuriyah, Nimatul; Prasetyo, Stefanus Eko; Sijabat, Abner Onesimus (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
With the growth of increasingly innovative technology, new media have been created to convey information, namely web applications. Current technology is needed to disseminate information widely and without borders. A web server being paralyzed can disrupt the client's process of accessing information. Web server paralysis can be caused by several attacks, one of which is Distributed Denial of Service (DDoS). The author uses Kali Linux as penetration testing software, using the GoldenEye tool as this tool can be used to test whether a site is vulnerable to DDoS attacks. Security design with Cloudflare involves implementing multiple layers of protection designed to mitigate security risks to applications and websites. In general, Cloudflare Web Application Firewall (WAF) is placed in front of the origin server to detect and block web-based attacks. Cloudflare's DDoS protection service is applied at a global layer, securing infrastructure from hacker attacks. Leveraging Cloudflare's infrastructure, this design provides an effective and efficient security solution against DDoS attacks, ensuring the availability and reliability of network services